(untitled) (Foro de Educacion, 2021)
Education policy rhythms are swiftly increasing in speed, policy contexts are becoming diffuse and policy actors are increasingly privatised. This article defends the thesis under a theoretical analysis dimension. Investigations in education require shifts in theory and analysis in order to understand the important transformations that are taking place in educational systems. Following the introduction, the paper examines previous aspects regarding rhythms, contexts and actors in the analysis of «policy transfers» in education. It then defends the need to study rhythms in education using the notions of «fast policies» and «neoliberalisation.» The two following sections focus on policy contexts. On one hand it touches on the subject of «policy assemblages» through its characteristic elements of multiplicities, the linking of diverse elements and non-linear ways of policy making. On the other hand, it shows how the notions of «policy mobility» and «policy mutation» are pertinent in order to analyse the uninterrupted movements and increasingly diffuse spaces in which education policies are created and put into action. The last section analyses the changes in private policy actors through the exploration of digital philanthrocapitalist governance in education.